Usability evaluation in a flight system: an approach based on Nielsen's heuristics - Martinez, Maria Soledad (2026)
This article presents the evaluation of usability in the Debriefing System, through the implementation of different assessment techniques. Each organization and software product are generally different, meaning that there is no a “unique” usability test that can be applied to all software projects. Therefore, each organization must select the usability technique that is most convenient for it, taking into account the characteristics of the software to be tested.  Usability can be evaluated using techniques that include the participation of end users, as is the case with the ISO 9241-11 standard, or it can be assessed using techniques that do not include their participation, such as heuristic evaluation.  In general terms, it is advisable to combine different methods in order to optimize the results. The objective of this work is to first perform a heuristic evaluation and then complement this test with a test involving end users, achieving a higher degree of reliability, completeness, and objectivity in the tests through this combination of techniques.